Platelet–lymphocyte ratio is a prognostic marker in small cell lung cancer—A systemic review and meta-analysis - Zhou, Hongbin; Li, Jiuke; Zhang, Yiting; Chen, Zhewen; Chen, Ying; Ye, Sa (Frontiers in Oncology, 2023)
Aim The aim of this study was to evaluate the relationship between platelet–lymphocyte ratio (PLR) and prognosis in small cell lung cancer (SCLC) patients. Method A comprehensive search was carried out to collect related studies. Two independent investigators extracted the data of hazard ratio (HR) and 95% confidence interval (CI) for overall survival (OS) or progression-free survival (PFS). A random-effect model was applied to analyze the effect of different PLR levels on OS and PFS in SCLC patients. Moreover, subgroup analysis was conducted to seek out the source of heterogeneity. Results A total of 26 articles containing 5,592 SCLC patients were included for this meta-analysis. SCLC patients with a high PLR level had a shorter OS compared with patients with a low PLR level, in both univariate (HR = 1.56, 95% CI 1.28–1.90, p < 0.0001) and multivariate (HR = 1.31, 95% CI 1.08–1.59, p = 0.007) models. SCLC patients with a high PLR level had a shorter PFS compared with patients with a low PLR level, in the univariate model (HR = 1.71, 95% CI 1.35–2.16, p < 0.0001), but not in the multivariate model (HR = 1.17, 95% CI 0.95–1.45, p = 0.14). Subgroup analysis showed that a high level of PLR shortened OS in some subgroups, including the Asian subgroup, the younger subgroup, the mixed-stage subgroup, the chemotherapy-dominant subgroup, the high-cutoff-point subgroup, and the retrospective subgroup. PLR level did not affect OS in other subgroups. Conclusion PLR was a good predictor for prognosis of SCLC patients, especially in patients received chemotherapy dominant treatments and predicting OS. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022383069.